Experimental study of the suppression of flaming combustion and thermal decomposition of model ground and crown forest fires; Combustion, Explosion, and Shock Waves; Vol. 53, iss. 6 - Volkov R. S. Roman Sergeevich (2017, 2017)
Title screen